SIFAT FISIK TANAH DI BAWAH TEGAKAN EBONI (Diospyros celebica Bakh.) DI DESA KASIMBAR BARAT KECAMATAN KASIMBAR KABUPATEN PARIGI MOUTONG - Marwan, Marwan; Yusran, Yusran; Umar, Husain (Jurnal Warta Rimba, 2015)
Soil physical properties strongly interrelate with the soils capability. Strength and carrying capacity of soils, ability fasten water absorb, drainage, penetration of root plant, aeration, and nutrient capture are mainly influenced by physical properties of the soils. Ebony species is classified into family of Ebenaceae that can have 40 m of height with 100 cm of breast height diameter and 4 m of buttress root. The objective of the research is to know the physical properties of the soils in the dale, inclined part, and top of the hill covered by ebony stand at West Kasimbar Village, Kasimbar sub district, Parigi Mautong district trough the period of April to June 2014. The methods of the research are filed orientation, deciding the soils sampling points below the stand and soils analysis in the laboratory. Purposive sampling was used to decide the locations of soil samples that were in the dale of the hill with 92 m of altitude, inclined part of the hill with 122m of altitude, and top of the hill with 130 m of altitude. Research location was in S: 00o07â€™24.4â€™â€™ and E: 199o56â€™52.5â€. The results of the research are the soils textur of the soil samples of the three parts of the hill are similar that is clay. The soils of the dale has 1,39 cm/hour of permeability, the inclined part: 6,08 cm/hour, and the top: 2,36 cm/hour. Soil porosity in the dale is 46,75%, 45,77% in inclined part, and 44,75% in the top. Bulk density of the soils in the dale is 1,41 gr/cm3, 1,44 gr/cm3 in the inclined part, and 1,46 gr/cm3 in the top. Organic matter of the soils is 3,08% in the dale, 2,45% in the inclined part, and 2,76% in the top. Keywords: soil physical properties, stand, ebony.